2023
DOI: 10.1177/08997640231191794
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of the Social Impact of Social Enterprises: A Systematic Review and Agenda for Future Research

Karen Quilloy,
Alexander Newman,
Amanda Pyman

Abstract: Despite growing research interest in the social impact of social enterprises (SEs), limited attention has been paid to the antecedents of social impact. To address this gap, we conducted a systematic review of 52 extant studies that examine the antecedents of SEs’ social impact. The paper synthesizes the antecedents identified from prior work and categorizes them into individual- and organizational-level factors. Based on the findings, we develop a future research agenda to advance our knowledge of the anteced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 125 publications
(279 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that businesses or other organisations that succeed in balancing these contrasting factors of innovation in sustainability are likely to demonstrate a higher ESP than those which focus on a single factor [57,58]. This theory is supported by other research, such as that by Tang et al [61] and Dressler and Paunovic [56], who argue that the expectations of stakeholders associated with ESP are constantly changing as the market evolves and organisations which are adept at exploration are more able to identify and seize new opportunities [62]. At the same time, effective exploitation allows firms to maximise the value of existing resources [57,58].…”
Section: Theoretical Backgroundmentioning
confidence: 63%
“…It has been suggested that businesses or other organisations that succeed in balancing these contrasting factors of innovation in sustainability are likely to demonstrate a higher ESP than those which focus on a single factor [57,58]. This theory is supported by other research, such as that by Tang et al [61] and Dressler and Paunovic [56], who argue that the expectations of stakeholders associated with ESP are constantly changing as the market evolves and organisations which are adept at exploration are more able to identify and seize new opportunities [62]. At the same time, effective exploitation allows firms to maximise the value of existing resources [57,58].…”
Section: Theoretical Backgroundmentioning
confidence: 63%